Association between Oesophageal Diverticula and Leiomyomas: A Report of Two Cases - Muhammad Chowdhry; Christina Spyratou; Bruno Lorenzi; Sritharan Kadirkamanathan; Alexandros Charalabopoulos (Case Reports in Gastrointestinal Medicine)
We report two rare cases of female patients presenting with oesophageal leiomyoma associated with oesophageal diverticulum, both of whom were surgically managed. Oesophageal leiomyoma and oesophageal diverticulum are uncommon as separate entities and rare as combined disease presentation. Clinicians need to be aware of the rare combination of the two entities and need to be able to exclude the presence of a tumour (benign or malignant) within a diverticulum and so plan the optimum treatment. Herein, we present two cases of oesophageal leiomyoma within oesophageal diverticulum and we try to elucidate the association between the two. To date, there is no consensus whether a diverticulum is secondary to a leiomyoma or, on the contrary, a leiomyoma arises within a diverticulum.